Assessment of Guar Gum Biopolymer Treatment toward Mitigation of Desiccation Cracking on Slopes Built with Expansive Soils. Issue 1 (January 2017) - Acharya, Raju; Pedarla, Aravind; Bheemasetti, Tejo V.; Puppala, Anand J.
Expansive soil embankments are prone to shallow slope failures caused by associated swell–shrink movements. Previous studies have confirmed that seasonal changes and corresponding volumetric changes are responsible for desiccation cracking, which is a major factor behind shallow slope failures of highway embankments. For the past few years, soil stabilization proved to be an effective way to mitigate the swell–shrink property of expansive clays. The current study addresses the feasibility of guar gum biopolymer in mitigating the swell–shrink behavior of clays and in turn making it possible to adopt them as stable geomaterials. The sustainable benefits of biopolymers far exceed the environmental benefits from conventional stabilizers that contractors typically use. This paper presents a comprehensive laboratory study, followed by finite difference modeling analysis, on biopolymeric guar gum–remediated expansive soils collected from shallow slope failure-prone areas. For this study, two dam locations, at Grapevine Lake and Joe Pool Lake, Texas, that were originally constructed with expansive soils, were considered. The engineering performance of biopolymer-treated soils was evaluated and an optimum dosage was recommended for mitigating desiccation cracking at the test sites. Slope stability analyses were conducted using Fast Lagrangian Analysis of Continua in Three Dimensions software by adopting laboratory-determined strength parameters to determine the range of the factor of safety for the slopes. The variation of the factor of safety computed with the inclusion of enhanced engineering parameters from guar gum treatments revealed the advantages of adopting this treatment.